Surface water treatment process; a review on various methods - Moayedi, Hossein; Kim Huat, Bujang; Asadi, Afshin; Kemas Salleh, Zakariah; Moghaddas, Masoud (Electronic Journal of Geotechnical Engineering, 2011)
This review paper focuses on process of water treatment plants (WTP) using three different methods. It is focused on the comparing differences between traditional and new developed WTP models. For traditional system, settlement process is selected and it is compared with a new system including Lamella tube. Sungai Terip water treatment plant was selected as case study since both traditional (Settlement process) and modern technology (Dissolved Air Flotation, DAF) used. The raw water was collected from Sungai dam which was an earth dam. After aeration it is distributed to three different WTPs. The processes were reviewed and compared in order to find their efficiencies.